The role of mean platelet volume in patients with non-specific abdominal pain in an emergency department - Coskun, Adil; Yavasoglu, Irfan; Sargin, Gokhan; Ok, Ismail Murat; Bircan, Metin; Avcil, Mucahit; Kadikoylu, Gurhan; Bolaman, Zahit (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : Platelets play an important role in inflammation. Mean platelet volume (MPV) may be a useful parameter for inflammatory conditions, in differentiating between non-specific abdominal pain (NSAP) and conditions requiring surgery, or early diagnosis of abdominal pain as a serious problem for emergency services. Aim : To investigate the role of MPV on NSAP admittance to the emergency department. Material and methods : The study consisted of 330 patients (186 female and 144 male, with mean age 49 ±20 years) with NSAP and 249 patients with abdominal pain (144 female and 105 male, with mean age 49 ±19 years) applied to our emergency service and enrolled to our study. Medical history, physical examination, complete blood count (CBC), and biochemical parameters were evaluated. Haematological parameters were measured by Beckman Coulter LH 780 instrument. Data were compared using Student’s t test, and p < 0.05 was accepted as statistically significant. Results : The MPV were significantly lower in patients with NSAP than in others (p = 0.025). There was no significant difference between both sexes with regard to MPV (p > 0.05). Moreover, the other haematological parameters (haemoglobin, platelet, or WBC counts) were not statistically different between both groups (p > 0.05). Conclusions : The MPV may be a useful, simple, and inexpensive parameter to diagnose or differentiate between NSAP and other conditions.